The Influence of Diabetes Mellitus in Myocardial Ischemic Preconditioning - Paulo Cury Rezende; Rosa Maria Rahmi; Whady Hueb (Journal of Diabetes Research)
Ischemic preconditioning (IP) is a powerful mechanism of protection discovered in the heart in which ischemia paradoxically protects the myocardium against other ischemic insults. Many factors such as diseases and medications may influence IP expression. Although diabetes poses higher cardiovascular risk, the physiopathology underlying this condition is uncertain. Moreover, although diabetes is believed to alter intracellular pathways related to myocardial protective mechanisms, it is still controversial whether diabetes may interfere with ischemic preconditioning and whether this might influence clinical outcomes. This review article looks at published reports with animal models and humans that tried to evaluate the possible influence of diabetes in myocardial ischemic preconditioning.